Teaching English pronunciation - Kenworthy, Joanne (Longman, 1987)
The book deals with the basic principles of teaching pronunciation; intelligibility and its assessment; building awarenes and concern for pronunciation; the devoplment and extension of skills; the relationship between sounds and spelling; the integration of pronunciation teaching with rest of the syllabus. It also lists the specific problems entoutered by speakers of Arabic, Chinese, French, German, Greek, Italian, Japanese, Spanish and Turkish.